Estudio del comportamiento agronómico de cuatro variedades de pastos sometidos a distanciamientos de siembra en la zona de Puebloviejo, provincia de Los Ríos - Carriel Álava, Pablo Hugo (2014)
One of the main limitations is that ruminant production in Ecuador is the dry matter not uniform throughout the year caused primarily by production: the uneven distribution of rainfall, low nutrient availability at ground level, using adapted species and the lack of pasture management practices. The objective of this research was to evaluate the performance of planting distance on performance in several cultivars of pasture. In addition, an economic analysis was performed.